All-Optical Tuning of Fano Resonance for Quasi-BIC and Terahertz Sensing Applications - Wenyao Liu; Wei Li; Chenxi Liu; Enbo Xing; Yanru Zhou; Lai Liu; Yunbo Shi; Jun Tang (Applied Sciences, 2022)
The bound states in the continuum (BIC) support anomalous resonances in the optical or terahertz band with a theoretically infinite quality factor. Therefore, it has great application prospects in the field of sensors. However, the current regulation of BIC mainly relies on the asymmetry of the material structure, which requires high processing technology. The structure can hardly be effectively adjusted once it is formed. In this work, we propose a new metasurface consisting of an array rectangular hole structure combined with aluminum and photosensitive silicon, which supports quasi-BIC to achieve ultrasensitive sensing in the terahertz range. By introducing photosensitive silicon, the asymmetry of the structure is efficiently controlled by the light field, thus realizing the bidirectional continuous control from quasi-BIC to BIC-like states. Through the optimization of the structure, a class of highly sensitive terahertz sensing based on optical tuning is finally proposed. The narrow-band quasi-BIC resonance is sensitive to medium thickness and refractive index, and compared with pure metal structure, the sensitivity and dynamic range can be increased by 2.60 times and 2.63 times, respectively. Due to the high slope of the Fano lineshape, sensitivity can reach 9.41 GHz/RIU and 0.65 GHz/μm, respectively. Furthermore, this feasible and practical structure provides an ideal platform for highly sensitive sensing.